Improving Quality in Surgical Intensive Care: The Critical Impact of Intensivist Presence and the Semiopen Unit Model - Serdar Efe; Şenay Yiğit Avcı; Ekrem Kaya; Emel Yılmaz (International Journal of Clinical Practice)
Conclusion: This study proves that surgeon-intensivist collaboration and a semiopen model in ICUs play a critical role by reducing mortality, increasing resource utilization efficiency, and improving patient outcomes. Our findings emphasize the need to restructure SICU processes with a multidisciplinary approach.